Low grade serous ovarian carcinoma: identifying variations in practice patterns. (7th January 2019) - Siemon, John; Gershenson, David M; Slomovitz, Brian; Schlumbrecht, Matthew
Abstract : Objectives: Low grade serous ovarian carcinoma is a rare subtype of ovarian cancer with an indolent and chemorefractory course. As such, treatment strategies among practitioners are not uniformly known. The primary objective of this study was to identify differences in practice patterns among physicians who treat low grade serous carcinoma. Methods Materials: A de novo survey was distributed to members of the Society of Gynecologic Oncology. Questions about demographics, management of primary and recurrent disease, and use of consolidation therapy were included. Statistical analyses were performed using χ 2 and Fisher's exact tests. Results: 194 gynecologic oncologists completed the survey. Approximately two-thirds of respondents practiced in a university based setting and treated a high volume of ovarian cancers, including low grade serous carcinoma. 82% recommended somatic testing during treatment and 84% routinely sent patients for genetic counseling. Treatment preferences for primary disease varied by debulking status. 48% of practitioners used hormone antagonism as consolidation after primary treatment. Secondary cytoreduction was preferred for patients with platinum sensitive recurrence and a long disease free interval following primary treatment (P<0.001). Hormone antagonism was the preferred treatment for the first platinum resistant recurrence (54%), while a BRAF inhibitor was the preferred agent in platinum resistant recurrence in the presence of a known BRAF mutation (56%). Conclusions: There was significant variation in the preferred management of low grade serous carcinoma among practitioners. Further efforts to improve knowledge of this disease, identify optimal treatment modalities, and provide guidelines for management should be encouraged.